The Impact of Audit and Financial Factors on Audit Report Lag: Evidence from Local Governments in Central Java Province - Ul-Fadillah, Rahma; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
Users of local government financial statements can experience negative consequences. The purpose of this study is to test empirical evidence on audit findings, auditor switching, local government size, leverage, profitability, audit opinion, and audit quality on audit report lag in local governments in Central Java province. This study used 30 out of 355 local governments (districts and cities) in Central Java Province during 2020 to 2022, with a total sample size of 90. This study uses secondary data collected from the audit report of the Central Java Financial Audit Agency (BPK Jawa Tengah) from 2020 to 2022. Data is collected from the electronic database service of the Information and Documentation Management Officer (E-PPID) in. The Purposive Sampling technique was used to obtain samples, and the data was analyzed using Ordinary Least Squares (OLS). According to research, audit findings, local government size, leverage, and profitability affect local government audit reports. Many variables, including solvency and auditor experience, can be further investigated. In addition, dividing the city government depending on the location of the island will provide an interesting additional audit report delay study.